Reactive and eccentric strength contribute to stiffness regulation during maximum velocity sprinting in team sport athletes and highly trained sprinters. Issue 1 (2nd January 2020) - Douglas, Jamie; Pearson, Simon; Ross, Angus; McGuigan, Mike
ABSTRACT: This study investigated the role of reactive and eccentric strength in stiffness regulation during maximum velocity sprinting (Vmax) in team sport athletes compared with highly trained sprinters. Thirteen team sport athletes and eleven highly trained sprinters were recruited. Vmax was measured using radar, and stiffness regulation was inferred from modelled vertical and leg spring stiffness. Reactive strength (RSI) was determined from a 0.50 m drop jump, and an eccentric back squat was used to assess maximum isoinertial eccentric force. Trained sprinters attained a higher Vmax than team sport athletes, partly due to a briefer contact time and higher vertical stiffness. Trained sprinters exhibited a moderately higher RSI via the attainment of a briefer and more forceful ground contact phase, while RSI also demonstrated large to very large associations with vertical stiffness and Vmax, respectively. Isoinertial eccentric force was largely correlated with Vmax, but only moderately correlated with vertical stiffness. Reactive and eccentric strength contribute to the ability to regulate leg spring stiffness at Vmax, and subsequently, the attainment of faster sprinting speeds in highly trained sprinters versus team sport athletes. However, stiffness regulation appears to be a task-specific neuromuscular skill, reinforcing the importance of specificity in the development of sprint performance.